2011
DOI: 10.1007/s00520-011-1212-y
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and cancer—a qualitative study of Australian cancer survivors

Abstract: Fertility is an important concern for young cancer survivors. There is a need for strategies regarding information provision and support for cancer patients with regard to these concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 32 publications
4
81
0
7
Order By: Relevance
“…It is suggested that these different groups of patients might have special needs that are unmet during fertility preservation counselling [34]. Retrospective surveys of cancer patients' views suggest that the majority have a strong desire to be informed about fertility preservation and available options [31,38,39,40]. Moreover, concerns about infertility are not limited to patients who are young and childless or/and have a partner [41].…”
Section: Fertility Preservation Options For Female Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that these different groups of patients might have special needs that are unmet during fertility preservation counselling [34]. Retrospective surveys of cancer patients' views suggest that the majority have a strong desire to be informed about fertility preservation and available options [31,38,39,40]. Moreover, concerns about infertility are not limited to patients who are young and childless or/and have a partner [41].…”
Section: Fertility Preservation Options For Female Patientsmentioning
confidence: 99%
“…However, even women with positive attitudes about having children after cancer have fears that possible pregnancy would increase chances for cancer recurrence or transmitting the cancer risk to the future child [47,48]. On the other hand patients who already have children might focus more on survival than fertility preservation [40,42] and as a result might be less likely to be offered fertility preservation consultation [46,49]. Therefore, discussing cancer treatment implications on fertility and possible fertility preservation options as well as providing patients with decisional support would significantly help to improve cancer care and benefit the patients in any country.…”
Section: Fertility Preservation Options For Female Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertility is an important topic for many cancer patients in their reproductive age and especially for those patients with a desire to have (more) children (Lee et al, 2006;Peate et al, 2011;Penrose et al, 2012). Previous studies indicated that cancer-related infertility has a negative influence on the quality of life in cancer survivors.…”
Section: Introductionmentioning
confidence: 98%
“…6 The loss of fertility is a concern beyond the inability to have children; the loss affects cancer survivors regardless of their desire for children. 51 Further contributing to the lack of participation in one's fertility decisions are gender disparities that exist in patients receiving fertility information. 38 Since few women are receiving fertility information, females are provided little opportunity to participate in decisions about their future fertility, thus robbing them of their desires for children and normal lives after cancer.…”
Section: Practice Guidance For Fertility Preservationmentioning
confidence: 99%